Injury‐Triggered Blueing Reactions of Psilocybe "Magic" Mushrooms. Issue 4 (4th December 2019) - Lenz, Claudius; Wick, Jonas; Braga, Daniel; García‐Altares, María; Lackner, Gerald; Hertweck, Christian; Gressler, Markus; Hoffmeister, Dirk
Abstract: Upon injury, psychotropic psilocybin‐producing mushrooms instantly develop an intense blue color, the chemical basis and mode of formation of which has remained elusive. We report two enzymes from Psilocybe cubensis that carry out a two‐step cascade to prepare psilocybin for oxidative oligomerization that leads to blue products. The phosphatase PsiP removes the 4‐ O ‐phosphate group to yield psilocin, while PsiL oxidizes its 4‐hydroxy group. The PsiL reaction was monitored by in situ 13 C NMR spectroscopy, which indicated that oxidative coupling of psilocyl residues occurs primarily via C‐5. MS and IR spectroscopy indicated the formation of a heterogeneous mixture of preferentially psilocyl 3‐ to 13‐mers and suggest multiple oligomerization routes, depending on oxidative power and substrate concentration. The results also imply that phosphate ester of psilocybin serves a reversible protective function. Abstract : Magic mushroom blues : Hallucinogenic Psilocybe mushrooms turn blue when injured. We report that the phosphatase PsiP and the laccase PsiL degrade psilocybin and initiate blueing. MALDI‐MS and in situ NMR spectroscopy show that the blue color is due to a mixture of quinoid psilocyl oligomers, primarily coupled via carbon 5.